Activating transcription factor 3, an early cellular adaptive responder in ischemia/reperfusion-induced injury - Heng Lin; Ching-Feng Cheng (Tzu Chi Medical Journal)
Recent studies have reported that ischemia/reperfusion (I/R) may act in the immune system where an exaggerated inflammatory response is initiated. With the activation of the immune system, damage-associated molecular patterns migrate and adhere to the I/R region, consequently inducing multiorgan injury. Emerging data indicate that upon I/R, stress-inducible proteins, including activating transcription factor 3 (ATF3), play essential roles in signaling during antiapoptotic, antimigration, and anti-inflammatory processes. Accumulating data suggest that ATF3 may be a potential target in I/R- or inflammation-induced organ dysfunction. This minireview focuses on the emerging evidence of the roles of ATF3 in multiple organs including the kidney, myocardium, and brain following I/R injury. In addition, this review addresses the role of ATF3 in chronic inflammation-induced pathophysiologies such as diabetes and atherosclerosis.